Molecular Dynamics Study on Deformation Mechanism of Grain Boundaries in Magnesium Crystal: Based on Coincidence Site Lattice Theory - Saitoh, Ken-ichi; Kuramitsu, Kohei; Sato, Tomohiro; Takuma, Masanori; Takahashi, Yoshimasa (Journal of materials, 2018)
As for magnesium (Mg) alloys, it has been noted that they are inferior to plastic deformation, but improvement in the mechanical properties by further refinement of grain size has been recently suggested. It means the importance of atomistic view of polycrystalline interface of Mg crystal. In this study, to discuss the deformation mechanism of polycrystalline Mg, atomistic grain boundary (GB) models by using coincidence site lattice (CSL) theory are constructed and are simulated for their relaxed and deformatted structures. First, GB structures in which the axis of rotation is in [11¯00] direction are relaxed at 10 Kelvin, and the GB energies are evaluated. Then, the deformation mechanism of each GB model under uniaxial tensile loading is observed by using the molecular dynamics (MD) method. The present MD simulations are based on embedded atom method (EAM) potential for Mg crystal. As a result, we were able to observe atomistically a variety of GB structures and to recognize significant difference in deformation mechanism between low-angle GBs and high-angle GBs. A close scrutiny is made on phenomena of dislocation emission processes peculiar to each atomistic local structure in high-angle GBs.